A new comprehensive evaluation indicator of adsorbent for gas separation - Wei, Mengqi (Environmental technology, 2022)
To evaluate and compare the performances of different adsorbents for gas separation, an adsorbent comprehensive evaluation indicator (ACEI) is proposed. In the ACEI, the working capacity, selectivity, adsorption rate, regeneration and circulation parameters, stability during adsorption, and tolerance to impurities are considered, and some exponents are introduced to allow the ACEI to adapt to different adsorbent working conditions. To illustrate the applicability of the ACEI, the adsorption of CO2 and N2 was investigated on two kinds of activated carbons (ACs), which were used for gas purification and bulk separation. The ACEI is a better overall indicator than other currently used indicators to evaluate the performance of adsorbents